Marine Fungi from Langkawi Island, Malaysia - Zainuddin, Nazura; Aisyah Alias, Siti (Malaysian Journal of Science, 2005)
Four hundred and fourty four marine fungi have been reported [11] which comprised of arenicolous, foliicolous, algicolous and manglicolous. Recent investigation has increased our knowledge of the diversity and occurrence of marine fungi. Two aspects are addressed in this paper: i) manglicolous marine fungi distribution, ii) Comparison of the fungi recorded at Langkawi with other studied areas in Malaysia, host specificity and their biogeography. Seventy four lignicolous and manglicolous higher marine fungi were collected from various substrate of the North-East Langkawi Island. The most frequent fungi were Dactylospora heliotrepha Kohlm. & E. Kohlm., Hypoxylon oceanicum Schatz and Leptosphaeria australiensis (Cribb & Cribb) G. C. Hughes while Sarvoyella lignincola E. B. G. Jones & Eaton was frequently encountered. In the present study, we observed that the diversity of mangrove fungi is dependent on age of the mangrove materials, diversity of mangrove tree flora, host specificity and location of mangrove area. However, the total number of samples examined also determined the marine fungal diversity.